2002
DOI: 10.1081/ja-120004275
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Associated Factors Among Rural Adolescents in Costa Rica

Abstract: The objectives of this study, carried out in 1995, were to assess both licit and illicit substance use among rural male and female Costa Rican adolescents, and associated health, psychological, and psychosocial problems. A sample of 304 students from rural schools was randomly selected. The mean age for females was 14.7 years (S.D. = 1.71), and for males was 14.4 years (S.D. = 1.62). The data were collected using the Latin-American version of Drug Use Screening Inventory (DUSI). Results showed a high prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
1
6
0
4
Order By: Relevance
“…Similar to our results, studies conducted in Latin American countries found that, although substance abuse among rural adolescents was becoming more widespread, substance abuse was generally more common in metropolitan areas. 21 Having an immediate or extended family member who abused substances were influential individual risk factors for abuse of minor tranquilizers and biperiden by adolescents in our study, which was consistent with the results of previous research. 22…”
Section: Risk Factorssupporting
confidence: 94%
“…Similar to our results, studies conducted in Latin American countries found that, although substance abuse among rural adolescents was becoming more widespread, substance abuse was generally more common in metropolitan areas. 21 Having an immediate or extended family member who abused substances were influential individual risk factors for abuse of minor tranquilizers and biperiden by adolescents in our study, which was consistent with the results of previous research. 22…”
Section: Risk Factorssupporting
confidence: 94%
“…Estos resultados confirman, en lo general, otros estudios realizados con el DUSI-R en México y América Latina, en los que los trastornos de control conductual, los problemas familiares y la relación con pares que presentan conductas desviantes se identificaron como factores asociados significativamente con el consumo de drogas ilícitas (32)(33)(34)(35)(36)(37)(38). 8 Sin embargo, se presentan también algunos aspectos novedosos.…”
Section: Discussionunclassified
“…Estudios realizados con el DUSI en poblaciones latinoamericanas indican que el consumo de drogas ilícitas está relacionado principalmente con alteraciones de la conducta, problemas familiares y de ajuste escolar o laboral, el establecimiento de relaciones con amigos desviantes y que consumen drogas, y con un inadecuado uso del tiempo libre (33)(34)(35)(36)(37). Similares hallazgos se han obtenido en estudios realizados en la población mexicana, en los que se han identificado una mayor asociación entre el consumo de drogas, por una parte, y un bajo control conductual, la pertenencia a redes sociales disfuncionales, una baja adherencia escolar y, en menor proporción, un inadecuado uso del tiempo libre, por la otra (38).…”
Section: Forma De Citarunclassified
“…In comparison to females, males were more likely to use alcohol, tobacco, inhalants, marijuana, and illegal drugs; the odds ratio estimates were 1. 3, 2.1, 1.6, 4.1, and 3.2, clustering was noted in all countries for alcohol and tobacco use; it was also noted in Costa Rica, El Salvador, Guatemala, and Panama for illegal drug use. Conclusions.…”
mentioning
confidence: 84%
“…Background for this report now includes a growing body of research on the epidemiology of adolescent drug involvement in these countries of the Americas, with prior contributions by members of our own research group, and by others. As shown in Table 1, most of the published evidence is from Panama and Costa Rica (1)(2)(3)(4)(5)(6). For example, according to the 1996 Panama National Youth Survey over 40% of school-attending adolescents had started to drink alcohol, while a much smaller proportion had used marijuana and inhalant drugs; the use of cocaine (crack/coca paste) and heroin was quite rare (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%